PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 002 PULAU RAMBAI KAMPAR TIMUR - Susilawati '; Erlisnawati '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: This Research aims to improve the learning outcomes IPS of students in fourth graderes Elementary 002 Pulau Rambai 2014/2015 school year. The subjects were students Fourth Graderes of SD Negeri 002 Pulau Rambai by the number of students by 18 students. The study was a collaborative class action research with two cycles. Research data shows that the learning outcomes of students has increased, the cost of the activities of teachers in the first cycle by an average of 60% is sufficient category increased 15% to 75% both categories. In the second cycle increased by an average of 80% of both categories increased 10% to 90% of both categories very good. Student activity in the first cycle with an average 55% increase enough categories 10% to 65%. In the second cycle increased by an average of 75% of both categories increased 10% to 85% of both categories. Research data has increased, which prior to the act of problem based learning model Instruction (PBI) on the basis of the complete score of 6 people (33.33%) with an average of 56.11. First cycle increased with thorough reached 11 people (61.11%) with an average of 67.22. Cycle II increases with thorough reached 15 people (83.33%) with an average of 74.44. It can be concluded that in this research is "learning model when application to problem based Instruction (PBI) it can improve the results of social studies fourth graderes students of SD Negeri 002 Pulau Rambai "is acceptable.Keywords: Problem Based Learning Model of Instruction (PBI). Learning Result